Effect of Shear Wall Ratio to Interstorey Drift in Reinforced Concrete (R/C) Buildings With Flat Slab With Continuous Drop Panel - Sagliyan, Sibel; Sayin, Erkut; Yon, Burak (Pamukkale Univ, 2012)
In this study, effect of changing of the shear wall ratio to interstorey drift in multistory reinforced concrete buildings with flat slab with continuous drop panel depending on the local site classes is investigated. For that purpose. an R/C frame structure and three shear wall frame structures with different shear wall ratio which have 7 and 9 stories are designed. These structures are analyzed according to response spectrum analysis in Turkish earthquake code for four local site classes. According to the analysis results, interstorey drifts are determined and are compared with boundary values in the earthquake code. According to obtained results, it is seen that, values of interstory drifts lie below limit values for 7 storey models which have 1 % shear wall and 9 storey models which have 1.5 % shear wall. In analysis SAP 2000 structural analysis program is used.
Keywords: Local site class; Shear wall ratio; Interstorey drift; Flat slab with continuous drop pane